Analisis Pidana Tambahan Penurunan Pangkat Dalam Pembaharuan Kitab Undang-Undang Hukum Pidana Militer/KUHPM - Arief Fahmi Lubis (Universitas 17 Agustus 1945 Semarang, Indonesia, 2020)
Additional criminal threats added on top of the main criminal sanctions aim to prevent military members from committing violations. The aim of this research shows that to maintain discipline, the application of additional punishment must remain based on the principles of law and justice. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that this additional penalty is expected to provide a stronger incentive for military members to comply with established ethics and regulations, maintain military integrity and efficiency, and improve the public's image and trust in military institutions.